(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Students face a variety of academic, emotional, and social obstacles in an increasingly complex learning environment that call for adaptation and adversity in addition to cognitive intelligence. This study investigates the connection between higher secondary students’ Adaptive skills and their Adversity Quotient (AQ), a gauge of a person’s ability to overcome obstacles. AQ, introduced by Paul G. Stoltz (1997), reflects a person’s ability to withstand, adapt to, and recover from difficult situations, which plays a pivotal role in shaping students’ adaptive interactions and personal development. The study involved a stratified random sample of 400 Higher secondary students (204 male and 196 female) across various academic streams (Science, Commerce, and Humanities) from both government and private schools. The AQ Profile and a standardized Adaptive skills Scale were administered to assess the relationships between Adaptive skills and Adversity quotient and interpersonal competence. Descriptive and inferential statistics, including t-tests, and correlation analysis, were employed to interpret the data.